Penguatan Pendidikan Karakter Berbasis Tradisi Pesantren di Pesantren An Nuqthah: Upaya Membangun Generasi Berakhlak Mulia - Alfi, Nurfauzan; Koimah, Siti Mariyatul; Zahra, Nur Amalia (CV. Kurnia Grup, 2024)
This study aims to examine the strengthening of character education based on tradition at Pesantren An-Nuqthah. As a traditional Islamic educational institution, pesantren plays an essential role in shaping students' character through long-standing traditions. Values such as respecting teachers (ta'dzim), discipline in worship, and simple communal living form the foundation for character development. This research employs a qualitative case study approach, using in-depth interviews with teachers and students. The findings reveal that pesantren traditions effectively build students' noble character. However, challenges from modernization and the use of technology, especially social media, affect students' focus on character education. Nonetheless, the pesantren strives to stay relevant by balancing traditional values with the wise use of technology. This research is expected to provide insights into strengthening character education for students in the modern era.